Competent and Qualified Personnel and Service Delivery at the Local Government Level in Nigeria: A Conceptual Review - Matthew Funsho Bello; Abga Maina Mackson (JPAS (Journal of Public Administration Studies), 2022)
This paper examined the concept of competent and qualified personnel and service delivery at the local government level in Nigeria. One of the core reasons for the creation of local government in almost all countries of the world is to provide goods and services to the local population. Unfortunately, this third tier of government has performed abysmally in meeting the felt needs of those in their jurisdictions and this has been a major concern to public policy makers and various stakeholders. The method used to obtain data was through the secondary sources, findings suggest that service delivery at the local government level in Nigeria has been very poor due to lack of competent and qualified personnel, the resultant effect has been lack of accountability and transparency. Service delivery at the local government’s level suffered neglect because of institutional weakness and lack of competent and qualified personnel. Paradoxically, poor services are the social vices bedeviling the Nigerian society of which local governments is charged with the responsibility of mitigating; hence for the local government to perform its statutory function of service delivery efficiently, there must be a complete autonomy of local government both administratively and fiscally; and for service delivery to be realistic. There must be competent and qualified personnel with expertise through regular workshops, seminars and training for capacity building.